2010
DOI: 10.1248/cpb.58.872
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Induction by Cinchona Alkaloids in the Rhodium(II) Catalyzed O-H Insertion Reaction

Abstract: The catalytic insertion reaction into O-H bond with a-diazocarbonyl compounds via a metal-carbenoid intermediate is a very useful organic transformation for the synthesis of oxygen-containing compounds.1-3) Remarkable advances, including enantioselective insertion, have been made in catalytic C-H insertions with a-diazocarbonyl compounds using Rh(II) complexes. [4][5][6][7][8][9] However, only limited success has been achieved for asymmetric insertions into O-H bond. 2,[10][11][12] Recently, Fu and Zhou indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…42 Indeed Saito and coworkers have found that cinchona alkaloid additives can deliver enantiomeric excesses of up to 50% in the O-H insertion of a-diazoesters with water catalysed by achiral rhodium(II) catalysts. 41 The Zhou group have also recently discovered that BINOL-based chiral phosphoric acids deliver high levels of enantioinduction in N-H insertion reactions. 42 These promising initial findings suggest that XHI coupled with enantioselective protonation is an area poised for further development.…”
Section: Enantioselective Xhi Processesmentioning
confidence: 99%
“…42 Indeed Saito and coworkers have found that cinchona alkaloid additives can deliver enantiomeric excesses of up to 50% in the O-H insertion of a-diazoesters with water catalysed by achiral rhodium(II) catalysts. 41 The Zhou group have also recently discovered that BINOL-based chiral phosphoric acids deliver high levels of enantioinduction in N-H insertion reactions. 42 These promising initial findings suggest that XHI coupled with enantioselective protonation is an area poised for further development.…”
Section: Enantioselective Xhi Processesmentioning
confidence: 99%
“…[15][16][17] The Cu-catalyzed O-H insertion of α-diazo esters is useful for the construction of α-alkoxycarbonyl structures, which are found in natural products and biologically active compounds. [18][19][20] A highly enantioselective version of this reaction has recently been accomplished with bisazaferrocene I, 21) Spirobox II, 17,[22][23][24][25][26] or the imidazoindolephosphine ligand III [27][28][29][30][31][32][33][34] (Fig. 2).…”
Section: Highlighted Paper Selected By Editor-in-chiefmentioning
confidence: 99%
“…The Box ligands 4 with both planar and central chiralities proved to be unsuitable for Cu-catalyzed intermolecular ethanolic O-H insertion, therefore we next investigated the use of the Box ligands (S p )-1, with only planar chirality, in inter-and intramolecular aromatic O-H insertion reactions. For the intermolecular phenolic O-H insertion reaction of ethyl α-diazopropionate (7), 22,27) the enantioselectivity of the isopropyl-substituted ligand (S p )-1d was better than that of phenyl-substituted (S p )-1b, and 80% ee was achieved, with the S configuration being preferred 35) (Table 2, entries 1, 3). The insertion reaction proceeded smoothly at room temperature, and the use of CuCl as a Cu source gave the highest enantiocontrol, but the product yield was lower than that obtained with Cu(OTf) 2 (entry 6).…”
Section: Highlighted Paper Selected By Editor-in-chiefmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding product, a chiral α‐hydroxy ester is a key substructure of many naturally occurring compounds and active pharmaceutical ingredients (Figure ). It was demonstrated that through the combination of metal catalysts and chiral ligands ( Cinchona alkaloids, bisoxazoline, bisazaferrocene and imidazoindolephosphine etc. ), highly enantioselective insertions of α‐diazo compounds into the O–H bonds of alcohols, phenols, and water have been realized.…”
Section: Figurementioning
confidence: 99%